Pyrochars as promising soil ameliorants: Assessment of content and spectral properties of their lipid fractions - E.V. Smirnova; К.G. Giniyatullin; А.А. Valeeva; Е.S. Vaganova (Учёные записки Казанского университета: Серия Естественные науки)
The possibility of changing the qualitative composition of soil organic matter by introducing pyrochars with the high lipid content has been analyzed. The lipid fractions of pyrochar (11 samples) obtained from herbaceous and woody materials in two pyrolysis regimes – high-temperature (400–600 ?C) and low-temperature (<400˚C) – have been studied. The high content of lipid fraction extracted by the alcohol- benzene mixture is characteristic for low-temperature pyrochar and amounts to 2.78% for samples from switchgrass residues, as well as 3.38% for corn residues and 3.67% for birch wood. The lipid fractions have been studied by UV-visible and FT-IR spectrometry. Their spectra in the UV-visible range are characterized by an exponential increase in the absorption intensity with a decrease in the wavelength, on which individual absorption maxima of groups of individual compounds are superimposed. Using the methods of empirical modeling of the spectral regions, it has been shown that the low-temperature pyrolysis of woody and herbaceous material results in the multi-molecular pool of organic compounds soluble in the alcohol- benzene mixture. They are characterized by similar molecular weight and composition, which allows obtaining approximately the same spectra in the UV-visible range. The plant material used to produce of pyrochar influences the content of functional groups and individual organic compounds. The obtained data are in agreement with the results of FT-IR spectrometry. The IR spectra of the alcohol-soluble lipid fractions of low-temperature pyrochar from different plant material are of the same type, but differ in the content of individual functional groups.